Characterization of lactic acid bacteria and pathogens isolated from traditionally fermented foods, in relation to food safety and antimicrobial resistance in tribal hill areas of Northeast India - Dey, Tushar K.; Lindahl, Johanna F.; Sanjukta, R.; Milton, A.A.P.; Das, S.; Kannan, P.; Lundkvist, Å.; Sen, A.; Ghatak, S. (Hindawi Limited, 2023)
Traditional fermented food products are often connected to various indigenous tribes and thus vary due to ethnicity, geography, and natural resource availability. The indigenous tribes from India greatly rely on fermentation processes for food preservation, flavor, and nutrition. Fermented foods can provide health benefits but also pose risks from harmful microbes and contaminants that grow in the food due to poor hygiene. In this study, we identified lactic acid bacteria (LAB) in fermented food collected from Northeast India, assessed their beneficial properties, and highlighted the risk from food pathogens that have antimicrobial resistance traits. A total of 113 different samples of fermented food products were collected from the local markets of five Northeastern Indian states (Nagaland, Manipur, Meghalaya, Arunachal Pradesh, and Sikkim). Standard laboratory methods were used to isolate LAB and determine their probiotic properties, conduct coliform counts, and isolate presumptive staphylococci from the fermented food samples. Antimicrobial susceptibility was determined by using the BD-Phoenix 100 automated system. We isolated 30 LAB with probiotic potential. The average aerobic colony count in different fermented food was 4.4–7.7 log·cfu/g, while coliforms were present in 43% (49/113, 95% (CI 34–53)) of the food samples, indicating low-hygiene levels. Additionally, some food samples contained staphylococci with phenotypic antibiotic-resistance markers (MRS, HLMUP, BLACT, and STAMLS). This study indicates that probiotic bacteria could be present in traditional fermented food products of Northeast India, but contamination with staphylococci and other bacterial pathogens with antibiotic resistance traits could put the health of consumers at risk.